2005
DOI: 10.1016/j.jtcvs.2004.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the functional benefits of skeletal myoblast transplantation by means of coadministration of hypoxia-inducible factor 1α

Abstract: Induction of angiogenesis is an effective means of potentiating the functional benefits of myoblast transplantation, and hypoxia-inducible factor 1alpha can successfully achieve this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 34 publications
0
44
0
2
Order By: Relevance
“…In any case, vascularization is clearly required for long term graft survival, and several studies have found over-expression of vascular endothelial growth factor (VEGF) enhances grafted cell survival [74][75][76]. Interestingly, adenoviral over-expression of hypoxia inducible factor-1α (HIF-1α) [77] with grafted skeletal myoblasts increased graft cell number, blood vessel formation and cardiac function. Although direct pro-survival effects of HIF-1α expression in myoblasts may have occurred, another potential benefit is increased vascularization by angiogenic molecules induced by HIF-1α, such as VEGF.…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…In any case, vascularization is clearly required for long term graft survival, and several studies have found over-expression of vascular endothelial growth factor (VEGF) enhances grafted cell survival [74][75][76]. Interestingly, adenoviral over-expression of hypoxia inducible factor-1α (HIF-1α) [77] with grafted skeletal myoblasts increased graft cell number, blood vessel formation and cardiac function. Although direct pro-survival effects of HIF-1α expression in myoblasts may have occurred, another potential benefit is increased vascularization by angiogenic molecules induced by HIF-1α, such as VEGF.…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…This is consistent with a high rate of cell death, which is incompletely compensated for by in vivo proliferation within the scar. 15 Cell manipulations to increase graft proliferation, survival, and electrical coupling with the host tissue 16 look to further enhance safety and efficacy of myoblast engraftment. 17 Nevertheless, the majority of the patients still exhibited at least 1 improved segment at end of FU.…”
Section: Hagège Et Al Myoblast Transplantation In Ischemic Heart Failmentioning
confidence: 99%
“…23 More than 90% of autologous skeletal myoblasts underwent apoptosis or necrosis at 24 h after transplantation. 24 Therefore, a strategy to improve the survival and differentiation of transplanted cells in the infarction site is critical for improving the efficiency of stem cell therapy.…”
Section: Discussionmentioning
confidence: 99%